Parents’ Readiness to Change Affects BMI Reduction Outcomes in Adolescents with Polycystic Ovary Syndrome - Karen P. Jakubowski; Jessica J. Black; Nermeen E. El Nokali; Katherine A. Belendiuk; Tamara S. Hannon; Silva A. Arslanian; Dana L. Rofey (Journal of Obesity)
Evidence supports the importance of parental involvement for youth’s ability to manage weight. This study utilized the stages of change (SOC) model to assess readiness to change weight control behaviors as well as the predictive value of SOC in determining BMI outcomes in forty adolescent-parent dyads (mean adolescent age = 15 ± 1.84 (13–20), BMI = 37 ± 8.60; 70% white) participating in a weight management intervention for adolescent females with polycystic ovary syndrome (PCOS). Adolescents and parents completed a questionnaire assessing their SOC for the following four weight control domains: increasing dietary portion control, increasing fruit and vegetable consumption, decreasing dietary fat, and increasing usual physical activity. Linear regression analyses indicated that adolescent change in total SOC from baseline to treatment completion was not predictive of adolescent change in BMI from baseline to treatment completion. However, parent change in total SOC from baseline to treatment completion was predictive of adolescent change in BMI, (t(24) = 2.15, p=0.043). Findings support future research which carefully assesses adolescent and parent SOC and potentially develops interventions targeting adolescent and parental readiness to adopt healthy lifestyle goals.